Finite Element Study on Bearing Capacities of Hook-Bolt Joint of Assembled GRC Wall with Light Steel Skeleton Frame. Issue 6 (March 2019) - Tang, Zhirong; Zha, Xiaoxiong; Wang, Baolin
Abstract: A new assembled external wall is composed of two glass fiber reinforced concrete (GRC) panels and built-in light steel skeleton frames and a layer of filled insulated core materials. To connect this new wall to the main steel structure, the new hook-bolt joint is used. The finite element (FE) software ABAQUS was used to study the bearing capacities of hook-bolt joint under horizontal force and vertical force. The FE results show that under horizontal and vertical force, the hook-bolt joint shows good elastic-plastic behaviour. In the initial stage of displacement loading, there is slip displacement stage and the load is very small. After this initial stage, with the gradual increase of displacement, the load increases gradually. Larger stresses are mainly distributed at the intersection of the hook-shaped connector and the U-shaped connector. The vertical bearing capacity of the hook-bolt joint is about two times larger than that of horizontal one. These studies can provide referential basis for the design and application of the hook-bolt joint of the assembled wall with light steel skeleton frame.